Optimasi Rute Distribusi Dan Penentuan Jumlah Tenaga Kerja Kurir Di Umkm Kerupuk Mawar - Alfian Fitrah Bangun Maulana; Handy Febri Satoto (CV. ALIM'SPUBLISHING, 2026)
This study aims to optimize the distribution routes and determine the ideal number of courier workforces at UMKM Kerupuk Mawar, an MSME facing inefficiencies in product delivery. The existing delivery system operates without structural planning, leading to long travel distances, high fuel consumption, and uneven driver workloads. To address these challenges, this research integrates the Saving Matrix method to optimize vehicle routing and the Full-Time Equivalent (FTE) method to evaluate and determine the optimal courier capacity based on actual workloads. Data were collected through direct observation, measuring delivery times, activities, and geographical coordinates of 25 customer locations. The results from the Saving Matrix analysis successfully reshaped the distribution network into optimal circular routes (ritase), reducing the total travel distance by 29.58% and decreasing monthly fuel costs by IDR 1,181,700. Concurrently, the FTE analysis revealed that the existing couriers experienced underload conditions due to unorganized scheduling. By restructuring the workforce based on FTE index projections, the company can operate efficiently with 5 optimized couriers, balancing workload distribution and minimizing idle time. In conclusion, combining routing optimization and workload-based workforce planning provides significant cost efficiency and operational balance for small and medium enterprises.